Estrategias mediáticas de “despolitización” de las mujeres en la práctica política (O de cómo no acabar nunca con la división público/privado) - Bernárdez Rodal, Asunción (CIC. Cuadernos de Información y Comunicación, 2010)
This paper argues that, although the parity has been achieved in the executive branch in Spain, women who engage in politics are treated in a particular way by the media. This treatment is to push his public image to the territory of “private”, being the main representative strategy by which women become “depoliticized.” The aim of this paper is to analyze, through a series of practical examples, how these representations are specified formally (both verbal and iconic).
Keywords: Politics; Woman; Media Communication; Journalism